2020
DOI: 10.3390/jof6030108
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Approaches Reveal New Regulatory Networks in Aspergillus fumigatus Metabolism

Abstract: Systems biology approaches are extensively used to model and reverse-engineer gene regulatory networks from experimental data. Indoleamine 2,3-dioxygenases (IDOs)—belonging in the heme dioxygenase family—degrade l-tryptophan to kynurenines. These enzymes are also responsible for the de novo synthesis of nicotinamide adenine dinucleotide (NAD+). As such, they are expressed by a variety of species, including fungi. Interestingly, Aspergillus may degrade l-tryptophan not only via IDO but also via alternative path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…We recently proposed that mathematical modeling and reverse-engineered gene-regulatory networks from experimental data could be used to determine the interconnectivity of multiple metabolic fungal pathways ( Acerbi et al., 2020 ). Using continuous time Bayesian networks over a time-course gene expression dataset, we inferred the global regulatory network controlling Trp metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently proposed that mathematical modeling and reverse-engineered gene-regulatory networks from experimental data could be used to determine the interconnectivity of multiple metabolic fungal pathways ( Acerbi et al., 2020 ). Using continuous time Bayesian networks over a time-course gene expression dataset, we inferred the global regulatory network controlling Trp metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Using continuous time Bayesian networks over a time-course gene expression dataset, we inferred the global regulatory network controlling Trp metabolism. The model revealed that high Trp levels activate the Trp catabolic routes independently, whereas low levels may interconnect the different metabolic pathways Article ll OPEN ACCESS (Acerbi et al, 2020). Going forward, it is becoming evident that Aro pathway activation can disrupt lung tolerogenic responses.…”
Section: Discussionmentioning
confidence: 99%
“…There exist at least seven studies in Aspergillus fumigatus that examined different sets of regulatory relationships involved in specific biological processes (9)(10)(11)(12)(13)(14)(15)(16). For instance, Guthke et al studied the regulatory mechanism(s) that allows A. fumigatus to adapt to a dramatic temperature shift during the infection process; in their study they used an inferred GRN to hypothesize that erg11, a gene necessary for ergosterol synthesis, modulates the expression of genes encoding heat shock proteins and the allergen RPL3 in response to a temperature shift of 30 °C to 48 °C (9).…”
Section: Introductionmentioning
confidence: 99%
“…mRNA transcriptomic profiles) to reverse engineer GRN structure, offer a popular and cost-effective technique to provide an initial view of the GRN that can be experimentally verified. For example, Acerbi et al applied a computational method using the transcriptome of several A. fumigatus genes to infer the regulatory connections involved in tryptophan synthesis (11). Although these studies have shed light on GRNs in A. fumigatus, the datasets have been limited to specific environmental conditions (e.g., tryptophan, temperature).…”
Section: Introductionmentioning
confidence: 99%